Abundance Of Coral Reef Fishes In The Waters Of Gelasa Island, Central Bangka District - Ferizal, Jemi; Muftiadi, M. Rizza; Pamungkas, Aditya; Hidayat, Syahrin Imron; Maulana, Ervan; Hidayatullah, Muhammad Fajar; FERIZAL1, JEMI (Universitas Bangka Belitung, 2025)
Gelasa Island has a coral reef ecosystem as a habitat for biota including coral reef fish, turtles, and others. The coral reef has been damaged due to anthropogenic activities. The purpose of the study was to determine the percentage of coral reef cover and the abundance of coral reef fish. The study was conducted in March 2024 in the waters of Gelasa Island. The method used was UPT (Underwater Photo Transect) for coral reefs and UVC (Underwater Visual Census) for coral reef fish, and the PAST 4.03 application to determine the diversity, uniformity, and dominance index. The results of the study showed that the percentage of coral reef cover in the waters of Gelasa Island was in the good category with an average of 52.42%. The abundance of coral reef fish was 49,114 ind/ha in the very rare category. The highest abundance of coral reef fish species was Neopomacentrus anabatoides, Pomacentrus alexanderae, and Caesio cunning. Based on the category, major fish have the highest abundance. The diversity value is in the moderate category, the uniformity value indicates an unstable community, and the dominance value is in the low category.